Framework for success of online brand management: a systematic literature review - Bilro, R. G.; Loureiro, S. M. C. (World Review of Entrepreneurship, Management and Sustainable Development, 2016)
The aim of this study is to identify and analyse the main constructs and relations highlighted in previous studies to manage online brands for internet companies and propose a framework for online brand management. In order to achieve such aim, an extensive and systematic literature review was developed employing several quality criteria of the literature review, such as: time range, scope of the study and journal quality list. In this vein, eighteen core articles were extracted and deeply analysed. Based on these articles a conceptual framework on online brand management is proposed